Pollen micromorphology of eastern Chinese Polygonatum and its role in taxonomy by using scanning electron microscopy. Issue 7 (13th February 2021) - Ali, Maroof; Liu, Yu‐Jun; Xia, Qi‐Ping; Bahadur, Saraj; Hussain, Abrar; Shao, Jian‐Wen; Shuaib, Muhammad
Abstract: Although considerable progress has recently been made in the taxonomic study of Asparagaceae, but the Polygonatum remains one of the most poorly investigated genus. Therefore, the present study was designed with the aim, to document the pollen micromorphology of closely related Polygonatum taxa and its taxonomic significance. Pollen micro‐morphological features were observed using scanning electron microscopy—SEM). The pollen grains are monad, navicular, monocolpate, and radially symmetrical. A significant variation was observed in the exine sculpturing. Moreover, most of the Polygonatum taxa have perforate pollen while some of them were mixed with psilate to perforate, perforate to microreticulate, sometimes scabrate, gemmate with baculate. Hence, this study documented the pollen morphology of Polygonatum taxa and strengthens the taxonomic identification of the genus Polygonatum based on pollen characters, which helps and can be used as an additional tool for the correct identification and discrimination of the species of Polygonatum at generic and species level. Abstract : The micromorphological analysis was done on about 30 samples of Polygonatum species collected from the different geographical region in Eastern China To document the four different groups of P. crytonema in Group I (narrow), II (wide), III (hybrid), IV(early flower), To document a detailed micromorphological observation to strengthen the taxonomy of closely related taxa by using SEM techniques.